Comments on the use of computer symbolic algebra for theoretical physics - Kennedy, A. D. (Surveys in high energy physics, 1980)
We discuss some of the Algebraic Manipulation Programs currently available, mainly considering MACSYMA, SCHOONSCHIP, and REDUCE, from the viewpoint of high energy theoretical physics calculations. We try to explain why some problems are better suited by one type of program and others by another, and we suggest various features which would be beneficial if implemented in future computer languages of this kind. We also include an appendix giving a more quantitative comparison of the systems.